Single dose oral dexibuprofen [S(+)-ibuprofen] for acute postoperative pain in adults. - Moore, R; Derry, S; McQuay, H (2009)
BACKGROUND: Dexibuprofen (S(+)-ibuprofen) is a non-steroidal anti-inflammatory drug (NSAID) licensed for use in rheumatic disease and other musculoskeletal disorders in the UK, and widely available in other countries worldwide. It is an active isomer of ibuprofen. This review sought to evaluate the efficacy and safety of oral dexibuprofen in acute postoperative pain, using clinical studies of patients with established pain, and with outcomes measured primarily over 6 hours using standard methods. This type of study has been used for many decades to establish that drugs have analgesic properties. OBJECTIVES: To assess efficacy, duration of action, and associated adverse events of single dose oral dexibuprofen in acute postoperative pain in adults. SEARCH STRATEGY: We searched Cochrane CENTRAL, MEDLINE, EMBASE and the Oxford Pain Relief Database for studies to May 2009. SELECTION CRITERIA: Randomised, double blind, placebo-controlled clinical trials of oral dexibuprofen for relief of acute postoperative pain in adults. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed trial quality and extracted data. Pain relief or pain intensity data were extracted and converted into the dichotomous outcome of number of participants with at least 50% pain relief over 4 to 6 hours, from which relative risk and number needed to treat to benefit (NNT) were calculated. Numbers of participants using rescue medication over specified time periods, and time to use of rescue medication, were sought as additional measures of efficacy. Information on adverse events and withdrawals were collected. MAIN RESULTS: In the single included study, both S(+)-ibuprofen (dexibuprofen, an active isomer of ibuprofen) 200 mg and 400 mg gave high levels of response, with 31/51 (61%) and 35/50 (70%) respectively having at least 50% pain relief over 4 to 6 hours, compared with 2/25 (8%) with placebo. The median time to additional analgesic use was 5.8 hours, 6.1 hours, and 1.8 hours respectively. The numbers of participants was too small to calculate NNTs with any meaning. AUTHORS' CONCLUSIONS: The information from the single trial in acute postoperative pain suggests it to be a useful analgesic, but at doses not very different from racemic ibuprofen.